2022
DOI: 10.1186/s43161-021-00067-3
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone addiction and its impact on musculoskeletal pain in neck, shoulder, elbow, and hand among college going students: a cross-sectional study

Abstract: Introduction Prolonged physical exposure during smartphone usage results in poor posture causing pain in neck, shoulder, elbow, and hands. So, our aim was to investigate the effect of smartphone addiction on musculoskeletal pain. Methods This cross-sectional study was carried out by a random sampling method from recognized institute in Bangladesh and India. Three hundred twenty-six participants, including male and female, aged between 18 and 30 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
2
23
1
Order By: Relevance
“…The findings of this study revealed that musculoskeletal symptoms in the shoulder, elbow, and wrist/hand region were associated with smartphone addiction/overuse and are consistent with earlier research among similar populations [ 33 , 50 , 51 ]. Individuals who were categorized as experiencing smartphone overuse/addiction adopt faulty postures, as their necks are flexed and their elbows are unsupported during extensive use of their smartphones, resulting in profuse static load in the neck and upper extremities [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…The findings of this study revealed that musculoskeletal symptoms in the shoulder, elbow, and wrist/hand region were associated with smartphone addiction/overuse and are consistent with earlier research among similar populations [ 33 , 50 , 51 ]. Individuals who were categorized as experiencing smartphone overuse/addiction adopt faulty postures, as their necks are flexed and their elbows are unsupported during extensive use of their smartphones, resulting in profuse static load in the neck and upper extremities [ 16 ].…”
Section: Discussionsupporting
confidence: 91%
“…They discovered that smartphone use, especially for lengthy periods of time, negatively affected the joints in the fingers, particularly the thumb and the wrist. Our findings are consistent with those of a study by Ahmed et al (19) , which found that 29.2 percent of physiotherapy students experienced thumb pain as a result of excessive usage of smartphones.…”
Section: Table (1): General Characteristics Of the Participants And R...supporting
confidence: 93%
“…Constant pain in the hands and fingers could result, as could a decrease in blood flow and the delivery of nutrients to the muscles. It was stated by Ahmed et al (19) that texting in a stationary position for lengthy periods of time strains the hand muscles, causing pain. This study's findings that normal adolescent students' smartphone use is not correlated with their manual dexterity are corroborated by those of Petrigna et al (28) , who found that the amount of time young adults spend using smartphones did not affect their performance on the Peg Board Test.…”
Section: Table (1): General Characteristics Of the Participants And R...mentioning
confidence: 99%
“…8 With digital-medium dependency and advancements, users (84.6%) reported neck pain, with 52.7% experiencing NMSD due to text-neck, particularly among individuals 21–30 years. 9 Similarly, industrial workers (78%) with flexed neck postures re-ported chronic neck pain and decreased productivity. 10 Poor neck posture is a common side effect of modern lives, which frequently involves extended periods of sitting and the use of electronic gadgets.…”
Section: Introductionmentioning
confidence: 99%